The impact of functional electrical stimulation to the lower leg after a single botulinum toxin injection in children with a spastic equinus gait due to cerebral palsy - Seifart, Anja (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScPhysio (Physiotherapy))--Stellenbosch University, 2008.